The Empowerment Model in Managing the Old Ampenan City Area as a Cultural-Based Tourism Destination in Mataram City, West Nusa Tenggara Province (International Forum of Researchers and Lecturers, 2025)
This research aims to study and formulate a model of community empowerment in the management of the Ampenan Old Town area as a culture-based tourist destination in Mataram City. The study highlights the importance of achieving a balance between the preservation of cultural values, environmental sustainability, and the active participation of local communities in decision-making and destination management. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation studies. The findings suggest that there is strong potential in aspects of culture, history, and local wisdom, which can be optimized through an inclusive and participatory empowerment model. Furthermore, this research emphasizes the need for policies that support sustainable tourism while preserving cultural heritage. It also recommends strengthening local institutions, drafting derivative regulations, and recognizing the role of communities in tourism area governance to ensure long-term success and sustainability.